APLIKASI PENCARIAN LETAK ATM BERBASIS ANDROID DENGAN GIS DI KOTA BANDAR LAMPUNG - Orien Rindy Erika; Didik Kurniawan; Febi Eka Febriansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Smartphone is a primary need for everyone in the modern era. Various features and advantages are offered by smartphone to those who use it. Smartphone is also widely used to help people to support their activities and to accomplish their work. Within the development of technology, GIS (Geographic Information System) has come along to provide service of locating a position of something in particular or a place to go. It is also used to locate its user with the help of satellite signal.Â GPS can provide precise and accurate information on the position, speed, direction, and time. In this study, the researcher designs and builds an Android- based search application called ATM Maps utilizing GPS technology. This application allows you to search the location of ATMs in the city of Bandar Lampung by the way, by theÂ ATM and by the city of Bandar Lampung.Â In turn, users can avoid difficulty in finding the location of an ATM. This will be a great help particularly to those who do not reside in the city of Bandar Lampung. Furthermore, the application also displays the transfer code of each bank so as to assist users in making easier cash transfer. The application is developed utilizing parsing technique of XML Pull Parser. It compares the data stored in folder of Assets Project and that in the server. The conclusion of this study reveals that the ATM Maps is successfully constructed and proven to be useful for its users. It is indicated by excellent rating and comments of satisfaction on the Play Store. In this application, the data is stored in Project Assets folder in purpose of reaching easy and quick access. In the other hand, data updating for the applications can also be processed easily.Keywords: ATM Maps, Bank, GIS, Xml Pull Parser, parsing, assets, Play Store, Android, Smartphone, Bandar Lampung.